The Routledge anthology of climate fiction - Gillard, Bill (New York, NY: Routledge, 2025)
"The Routledge Anthology of Climate Fiction brings together key works from the Bible to the 20th-century, in an accessible resource for students and teachers alike. With a robust variety of works, including H. G. Wells, Clare Winger Harris, H. P. Lovecraft, Leslie F. Stone, Arthur Conan Doyle, The Routledge Anthology of Climate Fiction offers vital new perspectives and critical introductions all the way back to humanity's earliest surviving literary texts"--
Includes bibliographical references and index.
Keywords: Climatic changes -- Fiction; Speculative fiction; Ecofiction; Climate fiction; Short stories